2000
DOI: 10.1086/315400
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Symptomatic Coccidioidomycosis among Elderly Persons in Arizona, 1996–1997

Abstract: Because of the increase in incidence of coccidioidomycosis among the elderly in Arizona between 1990 and 1996, a case-control study was conducted to look at risk factors for disease among these persons. Cases (n=89) were persons aged > or =60 years with laboratory-confirmed coccidioidomycosis; 2 control groups were selected, the first by use of random-digit dialing (geographic controls, n=91) and the second by use of lists of persons with negative serologic coccidioidomycosis tests (laboratory-negative control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 14 publications
8
46
0
Order By: Relevance
“…The average age of the patients with active coccidioidomycosis was nearly 67 years. While this appears old, recent data indicate that symptomatic coccidioidomycosis is far more prevalent among those aged 60 years and over than among younger subjects (4,21). Because all patients with active coccidioidomycosis at the medical center were referred to the coccidioidomycosis clinic and were eligible for study, the older age most likely reflects the predisposition for symptomatic illness among an older age group rather than any other factor.…”
Section: Discussionmentioning
confidence: 99%
“…The average age of the patients with active coccidioidomycosis was nearly 67 years. While this appears old, recent data indicate that symptomatic coccidioidomycosis is far more prevalent among those aged 60 years and over than among younger subjects (4,21). Because all patients with active coccidioidomycosis at the medical center were referred to the coccidioidomycosis clinic and were eligible for study, the older age most likely reflects the predisposition for symptomatic illness among an older age group rather than any other factor.…”
Section: Discussionmentioning
confidence: 99%
“…In Arizona, while coccidioidomycosis is more likely to be reported in persons older than 60 years 45 , the incidence in patients younger than 20 years increased 121% from 1998 to 2001, a larger increase than in any other age group in that period 6 . A study in the American Indian population reported increased susceptibility to coccidioidal dissemination in children younger than 5 years old as compared to other age groups 46 .…”
Section: Impactmentioning
confidence: 97%
“…Age is one such aspect that has been identified. In Arizona, those greater than 65 years of age were found to have the highest incidence of infection [22]. Although this finding has not been fully evaluated given that much of the elderly population of Arizona is comprised of individuals who have relocated from non-endemic areas either on a seasonal or permanent basis.…”
Section: Agementioning
confidence: 99%
“…Although this finding has not been fully evaluated given that much of the elderly population of Arizona is comprised of individuals who have relocated from non-endemic areas either on a seasonal or permanent basis. Another case-control study of geographically matched controls revealed that each year lived in Arizona provided a 5 % decline in the risk for acquiring coccidioidomycosis [22]. The impact of the large influx of elderly individuals to Arizona from non-endemic areas may explain their disproportionate burden of disease given that the incidence of infection within California peaks between 40 and 49 years of age [23].…”
Section: Agementioning
confidence: 99%